Formulasi dan Uji Stabilitas Fisik Sediaan Hair Tonic Ekstrak Etanol Daun Pare (Momordica charantia L.) - Puspitasari, Adellia; Sulistyawati, Rini (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Bitter melon (Momordica charantia L.) contains flavonoid, saponin, alkaloid, polifenol, momoridicin, cucurbitacin glycoside and charantin. This study aims to determine the hair tonic formulation of bitter melon leaves extract and evaluate its physical stability. The hair tonic formulation was made bitter melon leaves ethanol extract variation concentration i.e FI 3 gram, FII 6 gram and FIII 9 gram,VCO, menthol, propylene glycol, tween 80, nipagin, nipasol and distilled water. Hair tonic physical stability test was cariied out for 12 days of storage and determined for organoleptic test, homogeneity, pH test and viscocity. Organoleptic test result showed FI, FII, FIII were slightly green, green intense green colour respectively, characteristic odor, and liquid form. The homogeneity test of the 3 formulas showed homogeneous results, the pH test of FI, FII and FIII had pH values of 6, 6 and 7. The viscosity test results obtained values of 12.5 cP, 11 cP and 11.50 cP. Formula II gives the best formula results with physical characteristics of green colour, characteristic odor, homogeneous, pH 6 and viscosity value of 11 cP.